The Importance of Defence Diplomacy in North South Relations and its Role in Defence and Security Landscape of a State - Khalid, Faiq (Cranfield University, 2022)
International relations, as a subject, mostly talks about war and peace. All schools of thought and theories, on one side, provide a lens to understand the power dynamics in the world, on the other hand, are interlinked and revolve around them. What matters in international relations is to avoid war and ensure peace. When it comes to peace, diplomacy is the best way and an imperative tool to achieve this important and necessary cornerstone of development. Interestingly, diplomacy is actually international relations. Due to globalization, non-traditional security threats and the Covid pandemic, the defence and security landscape of a state is among the most concerned area that requires rapid transformation and “out of the box solutions” to better equip itself to face the challenges. Defence diplomacy seems to be the most appropriate and right approach at the moment. Although the practice is being exercised for centuries it has never been as important as it is now. The research intends to find the potential benefits of defence diplomacy for the defence and security landscape of a state. In doing so, as a case study, the research focuses on the premier state from the global north who is practising defence diplomacy such as the UK and a developing state such as Pakistan from the global south. There are three core leverages that defence diplomacy provides to a state i.e., tactical, strategic and economic. The current defence diplomacy scholarship largely focuses on the tactical and strategic aspects whereas economic facets are never given due importance. Defence diplomacy provides a very important pillar to the defence industrial base of a state, and this industrial base do not act in isolation, it requires and develops sister industries which then boost economies. Defence diplomacy is practised by the most advanced nations with sound economic and financial standing in the world. The research intends to explore to what extent a developing state such as Pakistan can practice defence diplomacy keeping in view its economic situation and availability of resources. It is also evident that defence diplomacy has played a strategic role during the covid pandemic in the defence and security landscape of a state.
Keywords: Defence Diplomacy'; 'Military Industrial Complex'; 'North South Relations'; 'DSDS21'; 'DSDS21 3MT'; 'Defence Studies'; 'International Relations'